A collaborative autoethnography of developing a 'Cultural Stories' exercise for intercultural teaching in China. (3rd September 2022) - Chi, Ruobing; Zhang, Hongling; Kulich, Steve
ABSTRACT: Intercultural teaching often emphasizes exposure to and understanding of cultural differences. Although it acknowledges the importance of cultural self-awareness, little research has been done to explore how such a goal is achieved. This article adopts collaborative autoethnography (CAE) to explore the creation, development, and use of variations of the 'Cultural Stories' exercise to enhance cultural self-awareness in intercultural education. Three culturally diverse instructors (in background, generations, contact/integrated cultures) narrate developments of this process for foreign language teaching in China as creators, teachers, and researchers. Analysis focuses on: (1) transformative learning process and experience of using the 'Cultural Stories' exercise; and (2) enhanced pedagogical understanding of intercultural teaching in China gained through developing and using this exercise. Results indicate that: (1) cultural stories have the potential to shape or start transforming students' originally essentialized understanding of culture and identity, and (2) contextualized pedagogical implementation and reflective professional commitment help inspire and bring greater reflection or transformation to the teachers' understanding of intercultural teaching. Implications of this instructional intervention and the research process are also discussed.